2020
DOI: 10.5534/wjmh.190068
|View full text |Cite
|
Sign up to set email alerts
|

A Schematic Overview of the Current Status of Male Infertility Practice

Abstract: The practice of male infertility has dramatically evolved over the past few decades. This has been achieved after the realization of the important contribution the male counterpart holds in the couple's infertility. It is also supported by a number of breakthroughs in the diagnosis and treatment of this medical condition. Several tests to investigate sperm quality and function were introduced along with refinements and/or institution of novel surgical techniques that can correct several causes of infertility. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
46
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 78 publications
0
46
0
6
Order By: Relevance
“…This pathology has become a global health issue with a general prevalence of 15%, affecting one out of six couples of reproductive age. According to global statistics, male infertility is the cause of approximately 50% of infertility cases, either as a sole cause or in combination with a female infertility factor [ 85 ]. Semen analysis is the most widely technique used to determine male fertility, but it has become evident that, in many cases, a basic seminogram is insufficient to determine the fertility status of the male partner.…”
Section: Proteomic Landscape Of Sp: a Potential Indicator Of Spermmentioning
confidence: 99%
See 1 more Smart Citation
“…This pathology has become a global health issue with a general prevalence of 15%, affecting one out of six couples of reproductive age. According to global statistics, male infertility is the cause of approximately 50% of infertility cases, either as a sole cause or in combination with a female infertility factor [ 85 ]. Semen analysis is the most widely technique used to determine male fertility, but it has become evident that, in many cases, a basic seminogram is insufficient to determine the fertility status of the male partner.…”
Section: Proteomic Landscape Of Sp: a Potential Indicator Of Spermmentioning
confidence: 99%
“…It is known that human SPZ generate reactive oxygen species (ROS) in physiological amounts, which play a role in sperm functions during sperm capacitation, acrosome reaction and oocyte fusion [ 140 ]. However, an excessive production of ROS results in seminal oxidative stress with male infertility as a consequence [ 85 , 136 ]. As previously described, SP contains many proteins and metabolites that coat and protect SPZ from oxidative stress.…”
Section: Proteomic Landscape Of Sp: a Potential Indicator Of Spermmentioning
confidence: 99%
“…Infertility is defined as the inability of a couple to conceive after at least one year of unprotected intercourse. According to WHO statistics, the inability to procreate has been increasing in recent years, and many couples of childbearing age suffer from this problem [ 1 ]. Numerous studies have shown that women and men share equal responsibility in that situation, i.e., about 30% to 40% for each partner [ 2 ], the remaining share representing cases for which the origin of infertility cannot be attributed to one or the other partner.…”
Section: Introductionmentioning
confidence: 99%
“…A decrease in semen parameter values is expected from the age above 40 years old [ 29 ]. Similarly, the mean BMI in the analyzed sample was 23.74 (SD ± 2.56), with most of the individuals corresponding to the “normal weight” category, meaning that in this study the already known association of sperm parameters and a high BMI was not present [ 30 ]. Consequently, the observed decrease of semen parameter values occurs in an otherwise healthy population of possible fertile men.…”
Section: Discussionmentioning
confidence: 78%